1973
DOI: 10.1159/000122119
|View full text |Cite
|
Sign up to set email alerts
|

Deserpidine Antagonism by a Tripeptide, L-Prolyl-L-Leucylglycinamide

Abstract: The tripeptide, L-prolyl-L-leucylglycinamide (PLG) reverses the sedative effects of deserpidine in mice and monkeys treated with pargyline and DOPA. It is effective both orally and when injected intraperitoneally, some of its action possibly being exerted upon the catecholamine system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…One of these was the misconception that increasing the dose of a peptide necessarily increases its effect. We first observed that higher doses of a peptide can result in reduced or even absent effects compared with smaller doses in studies with MIF-1 (Pro-Leu-Gly-NH 2 ) in mice in 1971 (Plotnikoff et al, 1971), in monkeys in 1973 (Plotnikoff et al, 1973), and in human beings in 1974 (Ehrensing and Kastin, 1974), the last results being confirmed in a second clinical study in 1978 . The animal studies involved models of mental depression and Parkinson's disease.…”
mentioning
confidence: 90%
“…One of these was the misconception that increasing the dose of a peptide necessarily increases its effect. We first observed that higher doses of a peptide can result in reduced or even absent effects compared with smaller doses in studies with MIF-1 (Pro-Leu-Gly-NH 2 ) in mice in 1971 (Plotnikoff et al, 1971), in monkeys in 1973 (Plotnikoff et al, 1973), and in human beings in 1974 (Ehrensing and Kastin, 1974), the last results being confirmed in a second clinical study in 1978 . The animal studies involved models of mental depression and Parkinson's disease.…”
mentioning
confidence: 90%
“…The reaction conditions and work-up were the same as those described for 8. Recrystallization of the crude product from EtOAc gave 348 mg (50%) of 10: mp 168-170 °C; L-Prolyl-L-leucyl-L-prolinamide (11). The mixed anhydride prepared in THF from 15 (1.9 g, 5.3 mmol), NEt3 (0.53 g, 5.3 mmol), and isobutyl chloroformate (0.72 g, 5.3 mmol) was treated with a solution of L-prolinamide (0.6 g, 5.3 mmol) in THF (10 mL).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of analogue 6 an imino group has been substituted for the methylene group while in compound 7 an additional methylene group has been inserted into the peptide chain. In addition to these modifications, several analogues (8)(9)(10)(11) have been synthesized where either a thiazolidine or pyrrolidine ring system has been incorporated into the glycinamide portion of the molecule.…”
mentioning
confidence: 99%
“…It is active in tests of dopa-potentiation [1,21–23] and oxotremorine antagonism in mice [2426], and deserpidine antagonism in monkeys as well as mice [27]. It exerts these effects even when given orally to mice and monkeys [2729], and does not require the presence of the pituitary gland [1,24,28]. MIF-1 is also effective against the neurotoxin MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) that induces many of the clinical symptoms of Parkinson’s disease [30,31].…”
Section: Conceptsmentioning
confidence: 99%
“…Its half-life in human plasma is 5 days although in rat plasma it lasts only a few minutes, like other small peptides including the related Tyr-MIF-1 and endomorphins [109112]. Moreover, unlike most peptides, many studies have shown that MIF-1 is active orally in rodents [2729,113] as well as human beings [33,5254,114]. It is yet to be determined whether MIF-1 is a substrate for oligopeptide transporter (PEPT)-1 in the intestine and PEPT-2 in the choroid plexus, or both in the kidney.…”
Section: Conceptsmentioning
confidence: 99%